Effects of dietary n‐6/n‐3 fatty acid ratio on nutrient digestibility and blood metabolites of Hanwoo heifers. (22nd May 2015) - Kim, Dong Hyeon; Lee, Hyuk Jun; Amanullah, Sardar M.; Adesogan, Adegbola T.; Kim, Sam Churl
Abstract: The objectives of this study were to investigate the effects of dietary n‐6/n‐3 fatty acid (FA) ratio on digestibility, blood metabolites and FA profile of Hanwoo heifers. Fifteen Hanwoo heifers (22 ± 3 months old; 357 ± 69.7 kg) were randomly assigned to three dietary treatments with n‐6/n‐3 FA ratios of 2.07, 5.18 and 7.37. The animals were housed individually in digestion crates and fed total mixed rations at 2.2% of body weight for 2 weeks of adaptation and 1 week of collection. Treatment effects on in vivo digestibility, plasma metabolite and fatty acid profiles, and in vitro ruminal fermentation and fatty acid profiles were examined. In vivo digestibility was not affected ( P   >  0.05) by dietary n‐6/n‐3 FA ratio. However, in vitro dry matter digestibility and concentrations of total volatile fatty acids and propionate decreased ( P <  0.05) linearly with increasing n‐6/n‐3 FA ratio. Plasma insulin and progesterone increased linearly ( P  < 0.05), but linolenic acid and total n‐3 FA decreased linearly ( P  < 0.05) with increasing n‐6/n‐3 ratio. Increasing the dietary n‐6/n‐3 FA ratio can increase the n‐6/n‐3 FA ratio in plasma and ruminal fluid as well as plasma progesterone secretion.